Skilled Home Healthcare Clinician and Staff Perspectives on Communication With Physicians: A Multisite Qualitative Study. (May 2021) - Norton, Jonathan D.; Nkodo, Amelie; Nangunuri, Bhavana; Arbaje, Alicia I.; Pierotti, Danielle M.; Carl, Kimberly; Boyd, Cynthia M.; Leff, Bruce; Sheehan, Orla C.
Abstract : Communication between physicians who order, and clinicians who provide skilled home healthcare (SHHC), is critical to well-coordinated care. The views of SHHC staff on communication with physicians have not been well studied. The objective of this study was to explore how SHHC staff view the communication processes with physicians who order SHHC services. Using purposive and snowball sampling, we conducted semistructured interviews with 22 SHHC staff across multiple regions of the United States. Qualitative thematic content analysis was used to analyze the data. SHHC staff experienced significant barriers to effective communication with physicians, including not being able to communicate in a timely manner when necessary for patient care, and challenges identifying the correct physician to coordinate care and sign SHHC orders. Key strategies to enhance communication focused on creating standardized processes to streamline communication, setting expectations for response times in communication, and improving the Centers for Medicare & Medicaid Services Home Health Certification and Plan of Care form (commonly referred to as the "CMS-485"/Plan of Care). SHHC staff experience significant communication challenges with physicians who order SHHC services that can compromise care coordination and delivery. Modifications to workflows are urgently needed to improve efficiency and quality of communication, care coordination, and quality of care.